Employee Passion and Motivation: Their Impact on Performance in the Textile Industry in Jakarta - Kurniawan, Edy; Leonard Togatorop, Agus; Moeins, Anoesyirwan (International Journal of Advanced Multidisciplinary, 2024)
This study examines the influence of employee passion and motivation on performance within the textile industry in Jakarta. Given the competitive nature of the textile sector, understanding the drivers of employee engagement is crucial for enhancing productivity and quality. Utilizing a mixed-methods approach, data were collected through surveys and interviews with employees across various textile companies. The findings reveal a significant positive correlation between employee passion, motivation, and performance metrics such as productivity and product quality. The study highlights the role of intrinsic and extrinsic motivational factors, suggesting that fostering a passionate workforce can lead to improved organizational outcomes. Implications for management practices are discussed, alongside recommendations for future research in this area.